Diretrizes para estruturação de repositórios de objetos virtuais de aprendizagem fundamentadas nos princípios da arquitetura da informação - Silva, Edilson Leite da (2023)
Considering information as a fundamental resource for decision-making in contemporary society and digital technologies as indispensable tools to assist in the search, production, storage and sharing of information necessary for the construction of knowledge, the importance of their interconnection in all areas of knowledge. For the educational field, there are several digital technologies such as games, simulators, search systems, authoring software, virtual learning environments and objects, database/base/repository of data/information/objects, assistive technologies, among others, that can be used as digital educational resources to assist in the teaching and learning process. However, there are some problems, such as the lack of structure in repositories of virtual learning objects that prevent a more effective use of digital educational resources. Thus, the main objective of the research is to analyze how the principles of Information Architecture, Information Representation Structures and User Search Behavior can contribute to the structuring of Virtual Learning Objects Repositories. The methodology encompasses the verification of information architecture principles in relation to existing repositories of virtual learning objects; analysis of users' search behavior in these repositories, considering the activities of the integrative model; definition of a set of proposed guidelines for structuring; carrying out prototyping, considering the proposed guidelines and using information architecture deliverables. Data were collected through a questionnaire developed based on the activities of the integrative model, having been analyzed according to the comparative method. The main results of the research involve the definition of a set of guidelines, considering aspects of information architecture and its representation structures, in addition to user search behavior and a generic prototyping for repositories of virtual learning objects, using deliverables from the architecture of the information. Faced with the problem regarding the structuring of virtual learning objects, considering its complexity in terms of volume of information, diversity of types and formats of objects and variety of public, it is concluded that the research brings theoretical and practical contributions by presenting guidelines and a prototype for structuring the Repository of Virtual Learning Objects, enabling improvements in the process of searching, accessing and sharing Virtual Learning Objects.